2020
DOI: 10.22603/ssrr.2019-0113
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Progression of Degenerative Lumbar Kyphoscoliosis: A Retrospective Study

Abstract: Introduction:Degenerative lumbar kyphoscoliosis is a serious clinical condition that affects activities of daily living. This study aimed to investigate the age-related progression of nonoperative degenerative lumbar kyphoscoliosis, to clarify its final state in elderly people, and to identify factors associated with its progression.Methods: This retrospective longitudinal study included 115 nonoperative cases (mean age at first consultation, 70.9 years; range, 50-89 years). All were followed up for >6 years. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Other studies have shown a correlation between an increase in age and kyphosis as a direct result of the progressive decline in various types of structures, such as bones, muscles, ligaments, and tendons [8]. Additionally, aging increases the likelihood of developing scoliosis, which can be attributed to progressive degenerative diseases such as facet and progressive disc degeneration [20].…”
Section: Discussionmentioning
confidence: 98%
“…Other studies have shown a correlation between an increase in age and kyphosis as a direct result of the progressive decline in various types of structures, such as bones, muscles, ligaments, and tendons [8]. Additionally, aging increases the likelihood of developing scoliosis, which can be attributed to progressive degenerative diseases such as facet and progressive disc degeneration [20].…”
Section: Discussionmentioning
confidence: 98%
“…The Ishihara et al study revealed the mechanism in which the reported case with left convex thoracolumbar neuromuscular kyphoscoliosis was analyzed by CT scan and the results showed the deviation of the axis to the left side between the esophagus and the stomach. The study further elaborated on the improvements in the symptoms of GERD after surgical management of scoliosis in that patient [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified lateral translation as a risk factor for the progression of scoliosis [2][3][4] . In addition, lateral translation has been found associated with greater back and leg pain [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 98%